answersLogoWhite

0


Best Answer

-6x^2 - 78x - 252

Improved answer:

-6x+6x+7

When simplified = 7

User Avatar

Wiki User

โˆ™ 2010-02-01 17:22:39
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is -6x plus 6x plus 7?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is 7 plus 10 plus - 6X?

7+10+(-6x)=17-6x


Simplify 7x plus 7 plus 6x - 9?

7x + 7 + 6x - 9 = 13x - 2


4x plus 7 equals 6x plus -7?

4x + 7 = 6x -7 14=2x so x = 7 (plus a negative # is simply - that number)


What is 6x plus 7 equals -5?

6x+7 = -56x = -12x = -2


Simplify the variable expression 6x plus 1 plus 7 - 3?

Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5


What is x when 9x plus 7 equals 6x plus 25?

If: 9x+7 = 6x+25 Then: x = 6


-6x plus 3 equals -7-5x?

-6x+3 = -7-5x 7+3 = 6x-5x 10=x


What is the solution of 55 equals 6x plus 7?

55 = 6x + 7 so 48 = 6x so 8 = x


What is the quadratic function of x2 plus 6x-7?

x2+6x-7 = (x+7)(x-1) when factored


What is x2 plus 3x plus 7 equals 6x plus 18?

xx+3x+7=6x+18 xx+3x+7-(6x+18)=6x+18-(6x+18) xx-3x-11=0 Factors of -11: 1,-11 -1,11 Doesn't factor evenly, use quadratic


6x - 4 plus 7 equals -5?

6x-4+7=-5 6x+3=-5 6x=-8 x=-8/6 = -4/3


10x plus 7 equals 4x plus 49 what does x stand for?

10x + 7 = 4x + 49 6x + 7 = 49 6x = 42 x = 6


3x plus 7 equals 6x - 2?

3x + 7 = 6x - 2 Rearranging gives 6x - 3x = 7 + 2 3x = 9 x = 3


How do you solve 6x plus 3 equals -7-5x?

6x + 3 = -7 -5x 6x + 5x = -7 -3 11x = -10 x = -10/11


What is the answer for 56 equals 6x plus x plus 7?

7(9+x) myalgebra.com


What is -x2 plus 6x plus 7 equals 0?

A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}


6x - 8 plus 2x - 5 equals 7 - 2x?

6x - 8 + 2x - 5 = 7 - 2x ?


What the solution to 6x-4 plus 7 equals 5?

If: 6x-4+7 = 5 Then: x = 1/3


What is X if X -9 equals 6X plus 7?

If: x-9 = 6x+7 then x works out as -3.2


What is 6x plus 9 plus 5x minus 7?

11x + 2


What is 11x plus 8 equals 6x plus 43?

x=7


What is -3 plus 6x plus 7-4x simplified?

4 + 2x


What is x in 12x plus 6 equals 6x plus 48?

7


4x plus 8 plus 2x-7?

It is 6x+1 simplified


How do you solve 6x plus 18 plus 9x-25?

you just add 6x+9x to get 15x then minus 25 from 18 to get -7 thus the answer will be 15x-7